Analysis Of The Management Of Essential Care In Newborn - Nova Marianti Purba; Febriana Sari; Ingka Kristina Pangaribuan; Deni Roslina; Sitti Nurasiyah (Indonesian Health Issue, 2026)
Essential care in newborns is an important intervention to prevent complications and lower neonatal mortality. This study aims to analyze the implementation of essential care procedures for newborns at H. Adam Malik Hospital Medan City in 2025, including skin contact measures, umbilical cord care, infant bathing, vitamin K, eye ointment, and Hepatitis B (HB-0) immunization. : The study used a cross sectional design with a quantitative approach and involved 76 samples taken using the Slovin technique from a total population of 329 infants. Data were collected through observation, document analysis, and questionnaires on health workers, then analyzed univariately. The results showed that all essential care measures had been carried out with 100% coverage, except for HB-0 immunization which was only given to 90.8% of infants due to several clinical factors such as low birth weight. The implementation of essential care in general is in accordance with the Standard Operating Procedures (SOP) and WHO guidelines. There is a need to increase consistency in the administration of HB-0 immunization as well as continuous education for health workers and parents to improve the quality of neonatal services.